Medieval philosophy - Kenny, Anthony, 1931- (Kenny, Anthony John Patrick. New history of western philosophy ;, 2005)
Sir Anthony Kenny continues his magisterial new history of Western philosophy with a fascinating guide through more than a millennium of thought from 400 AD onwards, charting the story of philosophy from the founders of Christian and Islamic thought through to the Renaissance. The middle ages saw a great flourishing of philosophy, and the intellectual endeavour of the era reaches its climax in the thirteenth and fourteenth centuries, with the systems of such great thinkers as Thomas. Aquinas and John Duns Scotus. Specially written for a broad popular readership, but serious and deep enough to.